PATHOMORPHOLOGICAL CHANGES IN THE VESSELS OF THE HEART AND THE LUNGS IN PNEUMOCONIOSIS - Надежда Николаевна Михайлова; Олег Иванович Бондарев; Мария Сергеевна Бугаева (Медицина в Кузбассе, 2017)
Subject – pathomorphological changes in the vessels of the heart and the lungs in pneumoconiosis.